2019
DOI: 10.1186/s41077-019-0100-2
|View full text |Cite
|
Sign up to set email alerts
|

Improving the relational aspects of trauma care through translational simulation

Abstract: Background Major trauma care is complex and requires individuals and teams to perform together in time critical, high-stakes situations. Scenario-based simulation is well established as a strategy for trauma teamwork improvement, but its role in the relational and cultural aspects of trauma care is less well understood. Relational coordination theory offers a framework through which we aimed to understand the impact of an established trauma simulation programme. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…Although it is becoming a more popular tool in quality improvement, simulation’s ability to shape relationships and culture in work environments has not been well studied. These and other reflection on translational simulation by our participants strongly suggest that a thoughtfully designed programme can directly target each domain of RC, with particularly impressive implications for the development of mutual respect between groups 25. The potential for simulation to shape culture is in keeping with previous research in the medical school context 27.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Although it is becoming a more popular tool in quality improvement, simulation’s ability to shape relationships and culture in work environments has not been well studied. These and other reflection on translational simulation by our participants strongly suggest that a thoughtfully designed programme can directly target each domain of RC, with particularly impressive implications for the development of mutual respect between groups 25. The potential for simulation to shape culture is in keeping with previous research in the medical school context 27.…”
Section: Discussionsupporting
confidence: 72%
“…*Previously published in our article “Improving the relational aspects of trauma care through translational simulation” published under the Creative Commons 4.0 Licence 25…”
Section: Resultsmentioning
confidence: 99%
“…Given our existing relationships with clinical services, our focus was on team and system challenges. We felt that our specific expertise in building relationships and shaping culture through simulation [7,8] was likely to be more important than ever as we undertook rapid and urgent high stakes change. Our strategy was aligned with the Queensland Health Pandemic Influenza Plan [9] and guided by the local Health Emergency Operations Centre (HEOC), to whom we provided biweekly reports.…”
Section: Our Strategy Developmentmentioning
confidence: 99%
“…At the micro‐level more frequent, timely, accurate and problem‐solving face‐to‐face communication between units may be required. For instance, translational simulation (Brazil, Purdy, Alexander, & Matulich, 2019) and nursing rounds (Tobiano et al, 2019) have been shown to enhance comradery across units (Rosenbaum, 2019). Promoting more opportunities for secondment in other units could also enhance relationships (Dryden & Rice, 2008).…”
Section: Relevance To Clinical Practicementioning
confidence: 99%